Germination and early seedling growth of a medicinal plant giant milkweed (Calotropis gigantea) under salinity stress (International Journal of Agricultural Research, Innovation and Technology, 2024)
Giant milkweed (Calotropis gigantea L.) is a salinity and drought-resistant xerophyte that is widespread around the world and serves significant ecological and medicinal purposes. The research aimed to evaluate the influence of saline stress on germination characteristics and prompt growth attributes of seedlings of C. gigantea. Seeds were germinated under five salinity levels viz. 0, 6, 8, 10 and 12 dS m-1 and allowed to grow for 30 days for traits assessment. Germination percentage (GP), germination rate index (GRI), co-efficient of the velocity of germination (CVG), mean germination time (MGT), Timson germination index (TGI), shoot length (SL), root length (RL), seedling dry weight (SDW) and healthy seedling number at 30 days were found lower in the salt solution compared to the control condition. Mean germination time was expanded with the increment of salinity levels. TGI of C. gigantea sustained a significant positive linear regression with GP (r = 0.9881), GRI (r = 0.9923) and CVG (r = 0.7887) at P < 0.001, but MGT (r = 0.7855) at P = 0.005. The correlation coefficient among the germination traits revealed insignificant between RL and other germination traits (GP, CVG, MGT, and TGI) except GRI (r = 0.499*) and SL (r = 0.541*).  It is recommended that, as an emerging medicinal and fiber resource plant, C. gigantea can be cultured productively in coastal saline areas. Int. J. Agril. Res. Innov. Tech. 14(1): 10-17, June 2024